PANCASILA SEBAGAI LANDASAN POLITIK HUKUM KEBANGSAAN INDONESIA - Anang Dony Irawan; Banu Prasetyo (Jurnal Pendidikan Sosial Keberagaman, 2022)
The purpose of this paper is to find out how far the implementation of Pancasila in its function as a state ideology and how Pancasila is related to politics and its existence as the basis of Indonesian national legal politics. Pancasila as the basis of the state with the function of being the source of all sources of law, which means that the implementation of all aspects related to law in the state must pay attention to the existence of Pancasila. In the life of the nation and state, Pancasila is a view of life in all aspects of life. At this time, Pancasila dominantly plays a role as a benchmark and identity in state administration. The values ​​contained in Pancasila are made into ideology thanks to the unity of purpose in the struggle for independence for the nation. These values ​​must also be a reference in all policies made for the public interest. Politics is generally known as a phenomenon related to citizens concerning general decisions and power. Politics in Indonesia, which is a state of law, must of course be in accordance with the Pancasila ideology which has the basic values ​​of divinity, humanity, unity, democracy, and justice that are universal and permanent. The implementation of legal politics in accordance with the basis of the state will certainly be a policy that is in accordance with the ideals of democracy, which is to take large sides with the people as the holder of sovereignty in the state. Pancasila as a legal ideal must be used as the basis and purpose of every law in Indonesia.